Penjatuhan Hukuman Disiplin terhadap Pegawai Negeri Sipil yang Divonis Pidana di Kabupaten Kepulauan Mentawai - Sari Dewi (Perspektif Hukum, 2018)
Civil servants are required to be obedient and obedient to the applicable invitation rules. Without prejudice to the provisions in the written-invitation rules, a civil servant who is convicted of a criminal sentence and must process employment regulations. There were 12 civil servants in Mentawai Islands District who were sentenced to different cases, but not all were disciplined. The imposition of disciplinary punishment on civil servants convicted was carried out by the Regent of Mentawai Islands based on recommendations from MPP. Of the 12 civil servants who were convicted, only 5 civil servants were sentenced to discipline.The legal consequences of the status of civil servants who are not sentenced are still active and receiving a full salary. This condition led to the payment of salaries of civil servants who were convicted not in accordance with the provisions. For officials related to Prince PNS, there are no further provisions that are not related to education policy, so as to enable the Mentawai Islands District government to make regional regulations and adjust MPP institutions and improve competencies, there must be a process needed so that every civil servant convicted certainty of employment status.